RANCANG BANGUN SISTEM INFORMASI PENJADWALAN MATA PELAJARAN DAN PENGOLAHAN DATA NILAI SISWA PADA SEKOLAH DASAR (SD) NEGERI 02 KOTA BARU - M.TI, Indera (Jurnal Informatika, 2012)
In the State Elementary School 02 Kota Baru, lessons scheduled activities and processing data of the studentsâ value assisted with handwritten books and Microsoft Excel applications. System development methods used in this research is to design scheduling lessons and data processing using Model value SDLC (System Development Life Cycle) with four stages, namely planning, analysis, design, implementation and use of the fifth. The whole program is designed by using Visual Basic 6.0, Microsoft SQL Server as the database and Crystal Report 8.5 as the report. The results of thedesign research is easy and fast the process produce accurate and timelyinformation in order to provide solutions and convenience in schedulinglessons and the values data processing have not been applied properly on systems running at this time, then made application programming to resolve the problem faced SD N 02 New Cities in the information systems design of lessons scheduling and valuedata processingKeywords: Design and Implementation, Information Systems, Scheduling Subjects, Processing Value Data.